A WIFE’S ABUSE OF SHIGAT TAKLIK AS GROUNDS FOR DIVORCE ACCORDING TO THE SHAFI’I SCHOOL OF THOUGHT - Achyanoor; Muhammad Yusuf; Rahmatullah (ADISAM Publisher, 2026)
Taklik talak is a husband's promise that is hung on four conditions, mean leaving his wife for two consecutive years, not providing a obligatory maintenance for three months, hurting his wife's body, and not caring about his wife for six months. Taklik talak aims to protect the rights of the wife and guarantee them from discriminatory, arbitrary actions by men, abuse of shigat taklik by wives misuse to divorce if the wife is no longer happy with her husband. This paper aims to examines the sigat taklik abused by the wife for divorce in the view of the Shafi'i school. This type of research is normative-empirical legal research with a comparative approach and the object is the wife who abuses sighat taklik as a reason for divorce. In the view of the Shafi'i school of thought, a woman who hates her husband, then sues her husband for divorce without any reason is not permissible.